The Women and the Development of Inclusive Religious Education in the Srikandi Lintas Iman Community of Yogyakarta - Karwadi; Daimah (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
The involvement of women in acts of intolerance and radicalism disturbs religious harmony in Indonesia. The phenomenon of the Surabaya bombing involving women as the main perpetrators of acts of terrorism proves that acts of terrorism, which initially had a patriarchal masculine face, later made use of women with their feminine approaches. In such anxiety arises the Srikandi Lintas Iman Community in Yogyakarta, Indonesia. This community is an alternative for women in sowing the values ​​of diversity, tolerance, and peace among the people. For this reason, it is important to research this community. This study aims to determine the construction and implementation of inclusive religious education built by the interfaith heroine community and the role of women in the development of inclusive religious education. This type of research is qualitative research. The research approach used is the educational sociology approach. The results of the study show that the construction of inclusive religious education in the Srikandi Lintas Iman Community in Yogyakarta stands on the principles and implementation of humanism and democratic values ​​, which include pluralism, justice, equality, doing good to others, and honesty which is manifested in community activities. The implementation of inclusive religious education is classified into several activity groups; religious studies, interfaith dialogue, and interfaith cooperation while the role of women in the development of inclusive religious education in the Srikandi Lintas Iman Community includes the domestic role of the family and the transition role of social and religious communities.